2016
DOI: 10.1002/pmic.201600156
|View full text |Cite|
|
Sign up to set email alerts
|

Label‐free quantitative proteomic analysis of tolerance to drought in Pisum sativum

Abstract: Abiotic stresses caused by adverse environmental conditions are responsible for heavy economic losses on pea crop, being drought one of the most important abiotic constraints. Development of pea cultivars well adapted to dry conditions has been one of the major tasks in breeding programs. The increasing food requirements drive the necessity to broaden the molecular basis of tolerance to drought to develop pea cultivars well adapted to dry conditions. We have used a shotgun proteomic approach (nLC-MSMS) to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
(63 reference statements)
2
8
0
Order By: Relevance
“…[55][56][57] Thus, these proteins are also significantly increased in the resistant pea genotype (P665) in response to drought stress. 38 In addition to our proteomic results, histological studies 36 have shown P.…”
Section: Cell Wall Reinforcement and Detoxification To Restrict Pathogen Growthsupporting
confidence: 73%
“…[55][56][57] Thus, these proteins are also significantly increased in the resistant pea genotype (P665) in response to drought stress. 38 In addition to our proteomic results, histological studies 36 have shown P.…”
Section: Cell Wall Reinforcement and Detoxification To Restrict Pathogen Growthsupporting
confidence: 73%
“…Finally, transport proteins, such as the water channel protein aquaporins, have been associated with plant tolerance of biotic and abiotic stresses, to which they respond by regulating the movement of water and small molecules through plasma membranes and vacuoles [59]. Based on a proteomics strategy involving the identification of proteotypic peptides, some transport proteins have been proposed as markers of tolerance to drought [60] and resistance to Ascochyta blight [42] in pea. The proteins were assumed to induce signaling and transport processes as mechanisms to maintain homeostatic equilibrium and cope with stress.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the tolerant soybean cultivar showed a higher capacity in the reactive oxygen species-scavenging and in maintaining the energy supply as compared to that of the sensitive cultivar. Similarly, when the similar differential and quantitative proteomics approach was adopted to investigate the two contrasting cultivars in drought tolerance from both monocot plants, rice [118], wheat [119], maize [120], dicot plants, potatoes [121], pea [122], Brassica [123], chickpea [124], tobacco [34], and tea plant [125], it was found that these drought-related DAPs in general play a role in regulating carbohydrate, glutathione, amino acids, sucrose and nitrogen metabolism, redox homeostasis and ROS-scavenging, protein synthesis and processing (or upregulation of ClpD1 protease), defense and stress-response processes, photosynthesis, cell wall biogenesis and degradation, cytoskeleton metabolism and energy production. However, in this quantitative phosphoproteomics study, we found that the drought-tolerant cultivar SRPs (significantly regulated phosphoproteins) are mostly related to water transport and deprivation, methionine metabolic process, photosynthesis/light reaction, response to cadmium ion, osmotic stress and ABA (hormone) under drought treatment (Figures 4D and 5).…”
Section: Discussionmentioning
confidence: 99%